2020
DOI: 10.1177/0300891620937809
|View full text |Cite
|
Sign up to set email alerts
|

Clinical results of active scanning proton therapy for primary liver tumors

Abstract: Background: Evidence for the efficacy of radiation therapy for primary liver cancer is growing. In this context, proton therapy (PT) can potentially improve the therapeutic ratio, as demonstrated by recent clinical studies. Here we report the first European clinical experience on the use of PT for primary liver cancer. Methods: All patients treated for primary liver cancer in our center entered the analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Most PBS liver studies have involved fractionated proton therapy. Dionisi et al [ 7 ] reported on 18 patients with hepatobiliary tumors treated with 15 fraction PBS liver therapy with median dose 58 GyRBE. One-year local control was 90%, with excellent toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Most PBS liver studies have involved fractionated proton therapy. Dionisi et al [ 7 ] reported on 18 patients with hepatobiliary tumors treated with 15 fraction PBS liver therapy with median dose 58 GyRBE. One-year local control was 90%, with excellent toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The adherence of MDTB treatment decisions to guidelines recommendations has been shown to be suboptimal mainly in the case of advanced age, severe comorbidities and strategic tumor localization [77] , but also in relation to differences in the availability of the therapeutic options in every center [78] . The overall rate of guidelines violations may reach 40% [77] and, interestingly, the adherence rate drops with the increasing disease stages to less than 50% in the intermediate and advanced stages, according to an Italian study [79] . Our MDTB, for example, is "non-compliant" with guidelines offering stereotactic body radiotherapy (SBRT) or proton beam therapy (PT) [80] for local HCC ablation in case of contraindications to surgical resection or thermal ablation.…”
Section: Indications Of Tace In Mdtb-selected Hcc Patientsmentioning
confidence: 98%
“…Recently, published retrospective series demonstrated the feasibility, safety, and efficacy of PBS-PBT for treating HCC. Although only small retrospective series have been reported, most studies achieved high local tumor control (around 95% at one year) and low toxicity profiles [ 16 , 17 ]. Yoo et al [ 18 ] compared the outcomes of HCC patients treated with either PS-PBT or PBS-PBT.…”
Section: Proton Beam Therapy Techniquesmentioning
confidence: 99%
“…Although only small retrospective series have been reported, most studies achieved high local tumor control (around 95% at one year) and low toxicity profiles. 16,17 Yoo et al 18 compared the outcomes of HCC patients treated with either PS-PBT or PBS-PBT. After propensity score matching, they revealed no difference in toxicity, tumor control, or survival between patients treated with PS-PBT or PBS-PBT.…”
Section: Proton Beam Therapy Techniquesmentioning
confidence: 99%